Akad Murābaḥah; Konsep dan Pelaksanaan di Lembaga Keuangan Islam Modern - Ahmad Maulidizen (Reslaj : Religion Education Social Laa Roiba Journal, 2019)
Islamic banking in Indonesia has experienced significant growth, including assets, financing providedand the number of customers. Murābaḥah is the sale and purchase of goods at the original price with theagreed-upon profit. In murābaḥah the seller must tell the cost of the product he buys and determine anadditional level of profit. This research is a library research about the murābaḥah contract according tomuamalah fiqh and its application in modern Islamic financial institutions. Methods of collecting data indocumentation and various sources related to the murābaḥah contract are then analyzed inductively anddeductively. The results of the study are the murābaḥah foundation is the principle of buying and sellingwith a deferred payment system. Murābaḥah, as used in Sharia banking, is based on two main elements,namely the purchase price and related costs, and the agreement on mark-up (profit). Islamic banks adoptmurābaḥah to provide short-term financing to customers for the purchase of goods even though thecustomer does not have the money to pay. The murābaḥah financing portfolio in Islamic banks reaches 70-80%, but in practice there have never been any problems, including; collateral which is a problem of fiqh,risk dependency as a problem of the bank, bankruptcy and delay in payment are the problems of customers,and profits are too high, namely the problem of coming from the community. Therefore, Islamic banks mustmake improvements in the implementation to be in accordance with Sharia.Keyword : Murābaḥah, Financing Instruments, Modern Islamic Financing